Impact of socio-cultural practices on substance abuse amongst the rural youth : towards the development of a school-based intervention programme - Mabasa, Matimba Allan (University of Limpopo, 2018)
The scourge of substance abuse globally amongst the youth today is probably one of the most talked about risky health behaviours in history, and is increasing at an alarming rate. Socio-cultural practices contribute towards the use and abuse of substances by the youth in rural areas. The “Ke Moja” programme that dealt with youth substance abuse was rarely received in these areas. The researcher sought to study the impact of socio-cultural practices towards substance abuse amongst the youth to develop a school-based intervention programme. The researcher’s research methodology included a mixed methodological approach that is, exploratory-descriptive design. Stratified-systematic and purposive sampling methods were used to draw a sample from learners, educators, social workers and SGB members. The data collection methods employed was semi-structured interview schedule and questionnaires. Data was analysed using thematic analysis. The results reveal that alcohol and drugs serve as agents of socialisation in socio-cultural events. It was found that there are different types of traditional home-brewed beers that the youth abuse almost daily because they are cheap, easily accessible and available. The findings also reveal that socio-cultural events contribute towards substance abuse in rural areas. The study reveals that sociocultural events take place almost every weekend where the youth use substaces as agents of socialisation. The findings reveal that the need for socio-culturally appropriate substance abuse prevention programmes amongst the youth is important in rural areas. The programme is called “Hambanani” which literally means doing away with the use and abuse of substances. The researcher concludes that socio-cultural practices contribute towards the abuse of substances by the youth in rural areas. The researcher recommends that social workers implement a school-based intervention programme on the impact of socio-cultural practices towards substance abuse amongst the rural youth.
Thesis (Ph.D. (Social Work)) -- University of Limpopo, 2018
Keywords: Socio-cultural practices; Intervention programme; School-based; Substance abuse; The youth; Substance abuse -- South Africa -- Limpopo; Youth -- South Africa -- Social conditions; Youth -- Subtance abuse -- South Africa -- Limpopo